A Watershed-wide Investigation of the Biological Effects of Contaminants of Emerging Concern: A Case Study in the North American Great Lakes - Schoenfuss, H.L. (My University, 2017)
Dr. Schoenfuss will explore the effects of Contaminants of Emerging Concern (CECs) on resident fish species in the North American Great Lakes watershed. CECs include common pharmaceuticals, household products and industrial and agricultural chemicals known to cause harm to aquatic life. We analyzed nearly 500 surface water samples at 54 sites in tributaries of the Great Lakes Watershed to confirm the ubiquitous presence of CECs. A subsequent cluster analyses of commonly detected CECs in this data matrix suggests that the co-occurrence of approximately half of the CECs can be attributed to dichotomous urban or agricultural upstream land use. Almost 3,000 resident and caged sunfish (Lepomis ssp.) were collected from 27 of the 54 sampling sites and analyzed for indicators of stress associated with CEC exposure. Canonical correspondence analyses revealed that concurrent with indicators of toxic stress, biomarkers of reproductive potential declined. To further examine the population level consequences, fathead minnows (Pimephales promelas) were exposed in the laboratory for three generations to the empirically derived urban CEC mixture at three environmentally relevant concentrations. Taken together, this integrated series of studies provides a case study on how to develop a comprehensive assessment of the presence and biological effects of CECs across a continental watershed. Dr. Schoenfuss will close the seminar by providing a brief introduction to the research activities, facilities and educational programs found in the Department of Biological Sciences at St. Cloud State University.
Seminar
Keywords: Contaminants of Emerging Concern (CECs); pharmaceuticals; aquatic life; sunfish (Lepomis ssp.)